Growth performance, robustness against stress, serum insulin, IGF‐1 and GLUT4 gene expression of red tilapia (Oreochromis sp.) fed diet containing graded levels of creatine. (1st November 2020) - Wardani, Wira Wisnu; Alimuddin, Alimuddin; Junior, Muhammad Zairin; Setiawati, Mia; Nuryati, Sri; Suprayudi, Muhammad Agus
Abstract: The experimental diets containing five levels of creatine supplementation, namely control ( N  = 0 g/kg creatine), B1 (1.00 g/kg glycine), B2 (0.40 g/kg creatine), B3 (0.80 g/kg creatine) and B4 (1.20 g/kg creatine) were tested to red tilapia up to apparent satiation 3 times a day for 56 days. After the feeding trial, fish were stressed by air exposure for challenge test against stress. The results described that creatine supplementation improved final body weight, feed conversion ratio (FCR) and protein retention. Creatine supplementation decreased blood glucose, cholesterol and triglyceride levels ( p <  .05), indicating more effective usage of non‐protein energy. Furthermore, creatine supplementation also increased plasma insulin levels and upregulated IGF‐1 and GLUT4 gene expressions in the liver significantly; it also improved robustness against stress, which was shown by higher superoxide dismutase, higher postchallenge survival and plasma cortisol, malondialdehyde and lower glucose levels. In conclusion, creatine supplementation at a dose of 0.289–0.389 g/kg diet escalated fish growth and improved robustness against stress via improving the SOD activity in red tilapia.